O conceito de gênero nas políticas públicas que orientam atenção à saúde da mulher: revisão integrativa da literatura - Bustorff, Leila Alcina Correia Vaz (2010)
It was intended to look trough this integrative literature review the concepts of gender in policy attention to women´s health, published by the /ministry of Health, from 1980 to 2000. The question of approach to the concept of gender in public policies for women resizes the way of conceiving women and men, their social relationships, family and marital, with repercussions on the understanding of health issues, network services and proper health care said. The documents were selected by consulting materials available from the database of the Ministry of Health The choice of documents took place through the inclusion and exclusion criteria. After its application to sample consisted of 93 official materials of the area of Women's Health published by the Ministry of Health, from 1980 to 2000 and categorized in a table in chronological order. The data collected related to the issue and strategies for analysis were collected through a pre-printed form prepared and data were analyzed quantitatively and qualitatively. The results showed that quantitative analysis of the total sample, 16 (17.2%) were published in the 1980s, 18 (19.35%) in the 1990s and 59 (63.45%) in the 2000s. The distribution of materials in three decades, addressing the second concept of gender, were respectively 09 (representing 9.67% of total sample) in the 1980s, 12 (12.90%) in the 1990s, and 41 (44.08%) in the 2000s, totaling 66.65% of the total sample. It is observed from these results, an upward trend on the approach of the concept of gender in official publications focused on women's health for three decades. Qualitative analysis showed that the concept of gender has been constructed over the years by various themes that permeated to better understanding, have been classified into two main categories: the first called dominant cultural patterns and the evolution of the concept of gender and their sub-categories: Construction biological differences between sexes (sexual difference), the social construction of gender differences - gender relational design, Design and intrageneric intersectionality with race, ethnicity, sexual orientation, and income generation and Gender and Masculinity. The second category is called central gender relations and the impact on women's health, and emerged four subcategories: Gender Violence, Sexual and reproductive health - empowerment of women; Illness and death and the sexual division of labor and the feminization of poverty. The increasing growth of women's participation in social relations involving both the private and public policies leading to a new perspective on women and men, combined with the gender category. It was felt that government agencies that publish and provide materials in the field of women's health will gradually incorporating gender relations in their literary production, thus assisting the understanding of relationships between women and men and their links to health issues. In this sense, it is expected that the mainstreaming of gender concept promotes the expansion of actions to strengthen women's empowerment to address issues related to the historical construction of your submission, including health issues.